1996
DOI: 10.1152/ajpheart.1996.270.6.h2157
|View full text |Cite
|
Sign up to set email alerts
|

Transient outward and delayed rectifier currents in canine atrium: properties and role of isolation methods

Abstract: Although the dog is the principal species used for in vivo studies of atrial arrhythmias, little is known about currents governing canine atrial repolarization. Cells were isolated from dog atria by exposure to collagenase of tissue in vitro ("chunk cells") and by arterial perfusion ("perfusion cells"). Whole cell voltage clamp revealed transient outward K+ current (Ito1), Ca(2+)-dependent Cl- current (Ito2), and delayed rectifier K+ current (IK). Ito1 recovered rapidly and showed little frequency dependence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 0 publications
3
137
2
Order By: Relevance
“…We have also failed to identify IKr in rat atrial myocytes under normal ionic conditions, but could detect it in isotonic Cs¤ solution. To our knowledge, the presence of IKr in rat atrial myocytes is shown for the first time in the present study, although it has been reported previously in canine (Yue et al 1996), human (Wang et al 1994) and guinea-pig atrial myocytes (Horie et al 1990;Sanguinetti & Jurkiewicz, 1991 A, effect of E-4031 (5 ìÒ) on membrane currents. Nicardipine (1 ìÒ) was included in the bath solution.…”
Section: Discussioncontrasting
confidence: 39%
“…We have also failed to identify IKr in rat atrial myocytes under normal ionic conditions, but could detect it in isotonic Cs¤ solution. To our knowledge, the presence of IKr in rat atrial myocytes is shown for the first time in the present study, although it has been reported previously in canine (Yue et al 1996), human (Wang et al 1994) and guinea-pig atrial myocytes (Horie et al 1990;Sanguinetti & Jurkiewicz, 1991 A, effect of E-4031 (5 ìÒ) on membrane currents. Nicardipine (1 ìÒ) was included in the bath solution.…”
Section: Discussioncontrasting
confidence: 39%
“…Micrographs were digitized using Photoshop 7.0 (Adobe, San Jose, CA), and areas of fibrosis were analyzed using Image Pro Plus 4.5 Scion image software (Scion Co., Frederick, MD). Whole-cell patch-clamp studies In our study, experimental procedures were complied with previously developed methods (13)(14)(15). Another twenty rabbits were used for whole-cell patch-clamp studies.…”
Section: Histological Examinationmentioning
confidence: 99%
“…Hearts were excised and atrial cells isolated from RA pectinate muscles as previously described. 10 In vivo studies were performed in the first 8 control and 18 CHF dogs. Because performing both in vivo and in vitro studies in each dog greatly prolonged the experiments, subsequent dogs were used for in vitro study only, after it had been verified that in vitro results were similar whether or not they were preceded by in vivo study.…”
Section: Preparation Of Animal Modelmentioning
confidence: 99%
“…I K is very sensitive to isolation procedures, 10 and therefore, changes in isolation technique could contribute to differences in I K when several groups are compared. To minimize possible effects of time-dependent changes in enzymes, isolation procedure, etc, animals from each group were studied concurrently in an alternating fashion.…”
Section: Potential Limitationsmentioning
confidence: 99%